2018
DOI: 10.1177/1591019918809932
|View full text |Cite
|
Sign up to set email alerts
|

Very delayed discontinuation of telescoped Pipeline embolization devices: a case report

Abstract: Background Flow diversion with the Pipeline embolization device (PED) is a widely accepted treatment modality for aneurysm occlusion. Previous reports have shown no recanalization of aneurysms on long-term follow-up once total occlusion has been achieved. Case description We report on a 63-year-old male who had a large internal carotid artery cavernous segment aneurysm. Treatment with PED resulted in compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“… 4 However, the use of multiple PEDs has been correlated with device migration/foreshortening and limits control of pore density and porosity of the PED with unknown effects on flow diversion, all of which may interfere with long-term aneurysm occlusion. 5 Bohara et al 6 described the recurrence of a giant ICA aneurysm between PED segments at the 4-year follow-up despite angiographic occlusion at the 3-year follow-up. Coxon et al 7 reported on a recurrent MCA fusiform aneurysm with areas of dilation, which had previously been surgically treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 However, the use of multiple PEDs has been correlated with device migration/foreshortening and limits control of pore density and porosity of the PED with unknown effects on flow diversion, all of which may interfere with long-term aneurysm occlusion. 5 Bohara et al 6 described the recurrence of a giant ICA aneurysm between PED segments at the 4-year follow-up despite angiographic occlusion at the 3-year follow-up. Coxon et al 7 reported on a recurrent MCA fusiform aneurysm with areas of dilation, which had previously been surgically treated.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, only a few studies in the literature have described the recurrence of a once completely occluded fusiform aneurysm on follow-up. [6][7][8]…”
mentioning
confidence: 99%
“…describe a patient with a large aneurysm treated successfully with telescoping Pipeline devices that upon follow up was noted to recur. In both cases, recanalization was attributed to device migration resulting in uncovering of the aneurysm neck [ 1 , 2 ]. Trivelato et al.…”
Section: Discussionmentioning
confidence: 99%
“…A second case of recurrence has been reported, but the recurrence was attributed to stent migration and exposure of the aneurysm neck. 5 After reviewing the rarity of this situation and discussing the risks and benefits of interval treatment, the patient elected to undergo placement of a second PED across the neck of the recurrent aneurysm (19 months post-treatment, not shown). In anticipation of the procedure, she was restarted on dual antiplatelet therapy as prior.…”
mentioning
confidence: 99%
“…A second case of recurrence has been reported, but the recurrence was attributed to stent migration and exposure of the aneurysm neck. 5…”
mentioning
confidence: 99%